Violent Behavior Prior to Admission Is Not a Factor in Further Prolonged Length of Stay: A Retrospective Cohort Study in a Japanese Psychiatric Hospital - Kinoshita, Hidetoshi; Kuroki, Noriomi; Okada, Takayuki (Frontiers in Psychiatry, 2021)
Background This study assessed the hypothesis that violent behavior prior to admission prolongs psychiatric hospitalization and evaluated the likelihood of hospital discharge to a community care setting based on demographic and clinical factors, with an emphasis on violent behavior. Methods We retrospectively selected 362 patients who were involuntarily admitted to a psychiatric hospital in Japan from December 1, 2015 to November 30, 2017, stayed longer than planned, and underwent review by a multidisciplinary team. We assessed (a) education and marital status and history of substance abuse, (b) the presence/absence and type of violent behavior that led to hospital admission, and (c) the discharge criteria. We divided the subjects into groups according to whether they had demonstrated violent behavior prior to admission and compared demographic and clinical variables between the groups using bivariate analysis. We also analyzed data using the Cox proportional hazard model, defining discharge to the community as the outcome. Age, sex, and variables that were significant at a level of P < 0.05 based on Cox univariate analysis were included in the multivariate models using the forced entry method. Results The Violent group included 94 patients (26%). There were no significant between-group differences in age, sex, educational background, marital history, career history, or the history of substance abuse. However, hospitalization was significantly longer in the Non-violent group. The Cox proportional multivariate hazard ratios revealed that violent behavior prior to admission resulted in a higher probability of hospital discharge. Conclusion Violent behavior prior to admission did not significantly contribute to prolonged hospitalization in patients who deviated from the treatment plan and had exceeded the planned hospitalization duration. Our findings recommend caution when using violence and impulsiveness observed during the acute stage to predict the difficulty of long-term treatment.